Histological and Histomorphometric Human Results of HA-Beta-TCP 30/70 Compared to Three Different Biomaterials in Maxillary Sinus Augmentation at 6 Months: A Preliminary Report. (26th July 2015) - Annibali, Susanna; Iezzi, Giovanna; Sfasciotti, Gian Luca; Cristalli, Maria Paola; Vozza, Iole; Mangano, Carlo; La Monaca, Gerardo; Polimeni, Antonella
Abstract : Objective . The aim of this investigation was to examine the bone regenerative potential of newly biphasic calcium phosphate ceramics (HA- β -TCP 30/70), by assessing histological and histomorphometric results of human specimens retrieved from sinuses augmented with HA- β -TCP 30/70, and comparing them to anorganic bovine bone (ABB), mineralized solvent-dehydrated bone allograft (MSDBA), and equine bone (EB), after a healing period of 6 months. Materials and Methods . Four consecutive patients with edentulous atrophic posterior maxilla were included in this report. A two-stage procedure was carried out for sinus augmentation with HA- β -TCP 30/70, ABB, MSDBA, and EB. After 6 months, specimens were retrieved at the time of implant placement and processed for histological and histomorphometric analyses. Results . At histological examination, all biomaterials were in close contact with the newly formed bone and showed the same pattern of bone formation; the grafted granules were surrounded by a bridge-like network of newly formed bone. A limited number of ABB particles were partially covered by connective tissue. The histomorphometric analysis revealed 30.2% newly formed bone for Ha- β -TCP 30/70, 20.1% for ABB, 16.4% for MSDBA, and 21.9% for EB. Conclusions . Within the limitations of the present investigation, these results support the successful use of HA- β -TCP 30/70 for sinus augmentation.